Side effects and post-vaccine care against COVID-19 in healthcare personnel in Peru - Burga Ramírez, Esther Carolina (2024)
Objective: Describe the side effects and post-vaccine care against COVID-19 in health personnel in Peru. Method: Qualitative descriptive research, 12 primary care health workers obtained by the saturation and redundancy technique participated. The data was collected with a semi-structured interview guide, and manually processed through content analysis. Results: Three categories were obtained: a) Local and systemic effects post-vaccine against COVID-19, b) Variability, time of appearance and duration of side effects according to dose and type of vaccine against COVID-19, c) Post-vaccine care against COVID-19. Conclusions: Some of the side effects of the COVID-19 vaccine are the same as those expected in any vaccination process, none were serious and most subsided on their own, or with conventional medications. As health personnel experience, vaccination against COVID-19 was safe, which allows them to extrapolate and raise awareness among the general population regarding vaccination in new pandemics.